Variation of head circumference variation in preterm infants less than 34 weeks to histologic chorioamnionitis - Pellanne-Aro, Jean P. (2023)
Objective: To analyze the variations of head circumference (HC) in preterm infants, born with less than 34 weeks of gestation, exposed to histologic chorioamnionitis (CAH), and observed until 2 years of corrected age. Materials and methods: This is a cohort study derived from two prospective studies. The analyzed data corresponded to HC measures obtained from the subjects at three points: birth, 40 weeks, and 2 years of corrected age. The subjects were classified in two groups: exposed and not exposed to CAH. Preterm infants with CAH were divided according to its subtype in chorioamnionitis, subchorionitis and chorioamnionitis plus funisitis. Results: Out of 91 preterm infants included in the study. 41.8% (38/91) presented CAH. At birth, the average measure of HC in exposed infants was 27.7 cm (31,2 percentile), while in not exposed infants it was 28.3 cm. (42,1 percentile). At 40 weeks and at 2 years, the average measures were similar. The CAH chorioamnionitis subtype was found to be associated with PC growth retardation (p<0,05). A lesser gestational age (p=0.005) was related with greater cranial growth speed. Conclusions: Newborns younger than 34 weeks exposed to CAH had lower HC percentile at birth. We observed a recovery of HC at 40 weeks. The chorioamnionitis subtype was related to lower HC at 2 years of corrected age. Intrauterine growth  restriction (IUGR) enhanced this association at these three points, while sepsis did so only at 40 weeks. Further research is required to confirm these findings